2019
DOI: 10.1021/acschembio.9b00222
|View full text |Cite|
|
Sign up to set email alerts
|

Mitochondrial Protease ClpP is a Target for the Anticancer Compounds ONC201 and Related Analogues

Abstract: ONC201 is a first-in-class imipridone molecule currently in clinical trials for the treatment of multiple cancers. Despite enormous clinical potential, the mechanism of action is controversial. To investigate the mechanism of ONC201 and identify compounds with improved potency, we tested a series of novel ONC201 analogues (TR compounds) for effects on cell viability and stress responses in breast and other cancer models. The TR compounds were found to be ∼50–100 times more potent at inhibiting cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
199
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(242 citation statements)
references
References 39 publications
15
199
1
5
Order By: Relevance
“…Compared to ADEP1, a known activator of bacterial ClpP and human CLPP (Brötz-Oesterhelt et al 2005;Wong et al 2018), the imipridones were at least 20-fold more potent in these in vitro assays ( Figure S1D). These results demonstrate that ONC201 and ONC212 inhibit human cell proliferation by inducing unregulated CLPP proteolytic activity, as recently shown in other studies (Graves et al 2019;Ishizawa et al 2019).…”
Section: Onc201 and Onc212 Activate Clppsupporting
confidence: 90%
See 3 more Smart Citations
“…Compared to ADEP1, a known activator of bacterial ClpP and human CLPP (Brötz-Oesterhelt et al 2005;Wong et al 2018), the imipridones were at least 20-fold more potent in these in vitro assays ( Figure S1D). These results demonstrate that ONC201 and ONC212 inhibit human cell proliferation by inducing unregulated CLPP proteolytic activity, as recently shown in other studies (Graves et al 2019;Ishizawa et al 2019).…”
Section: Onc201 and Onc212 Activate Clppsupporting
confidence: 90%
“…CLPX also performs chaperone functions independently of CLPP, as it promotes heme biosynthesis and enhances the DNA-binding activity of TFAM, a mitochondrial transcription factor (Kasashima et al 2012;Yien et al 2017). TFAM itself was also depleted in response to ONC212, in agreement with previous studies in other cell lines (Greer et al 2018;Graves et al 2019). Consistent with previous reports of mitochondrial defects caused by ONC201 treatment in various cell lines (Greer et al 2018;Ishizawa et al 2019), we found that both ONC201 and ONC212, but not an inactive isomer of ONC201, caused a collapse of mitochondrial membrane potential and an increase in mitochondrial reactive oxygen species levels in NALM-6 cells ( Figure S3).…”
Section: Effect Of Clpp Activation On the Human Proteomesupporting
confidence: 88%
See 2 more Smart Citations
“…Follow-up studies discovered that ONC201 did not directly activate TRAIL in all of the cancer cells in which it was effective but was impairing mitochondrial function [75]. Recent data from two studies identified the target of ONC201 as being the mitochondrial CLPP protease which is activated by ONC201 and results in increased cancer cell killing [76,77].…”
Section: Toxic Effects Of Pharmacological Agents On Mitochondrial Funmentioning
confidence: 99%